On the epistemology of resilience in public health: a novel perspective in a changing world - Jatobá, Alessandro; Castro-Nunes, Paula; Rodrigues de Carvalho, Paulo Victor (Frontiers in Health Services, 2025)
This review proposes the foundations for an epistemology of resilience in public health, addressing the need for a theoretical framework to guide research and policy. Resilience, often ambiguously defined, is reexamined here as a critical attribute of public health systems, enabling them to adapt, absorb, and respond to routine and extraordinary demands without compromising universal and equitable service delivery. By integrating logical, sociological, historical, and philosophical perspectives, the paper delineates resilience as a structured and measurable concept, distinguishing it from common ambiguities in academic and policy discourse. It further introduces a set of foundational axioms to clarify the boundaries of resilience and support its operationalization within public health. These axioms emphasize the interplay between structural and functional dynamics, responses to internal and external stressors, and the importance of systems-level design over reliance on individual adaptations. This epistemological approach aims to bridge the gap between theory and practice, providing a robust basis for developing evidence-based policies that strengthen public health systems' ability to meet evolving challenges while promoting equity and universality.